Absence of Cytochrome P450-1b1 Increases Susceptibility of Pressure-Induced Axonopathy in the Murine Retinal Projection - Amirmokhtari, Naseem; Foresi, Brian D.; Dewan, Shiv S.; Bouhenni, Rachida A.; Smith, Matthew A. (Frontiers in Cell and Developmental Biology, 2021)
Mutations in the cytochrome P450-1B1 (Cyp1b1) gene is a common genetic predisposition associated with various human glaucomas, most prominently in primary congenital glaucoma (PCG). The role of Cyp1b1 in the eye is largely unknown, however, its absence appears to drive the maldevelopment of anterior eye structures responsible for aqueous fluid drainage in murine models. Nevertheless, vision loss in glaucoma ultimately results from the structural and functional loss of retinal ganglion cells (RGCs). Cyp1b1’s influence in the development and support of retinal ganglion cell structure and function under normal conditions or during stress, such as elevated ocular pressure; the most common risk factor in glaucoma, remains grossly unknown. Thus, to determine the role of Cyp1b1 in normal retinal projection development we first assessed the strucutrual integrity of RGCs in the retina, optic nerve, and superior colliculus in un-manipulated (naïve) Cyp1b1-knockout (Cyp1b1–/–) mice. In addition, in a separate cohort of Cyp1b1–/– and wildtype mice, we elevated and maintained intraocular pressure (IOP) at glaucomatous levels for 5-weeks, after which we compared RGC density, node of Ranvier morphology, and axonal transport between the genotypes. Our results demonstrate that naïve Cyp1b1–/– mice develop an anatomically intact retinal projection absent of overt glaucomatous pathology. Following pressure elevation, Cyp1b1–/– accelerated degradation of axonal transport from the retina to the superior colliculus and altered morphology of the nodes of Ranvier and adjacent paranodes in the optic nerves. Together this data suggests the absence Cyp1b1 expression alone is insufficient to drive murine glaucomatous pathology, however, may increase the vulnerability of retinal axons to disease relevant elevations in IOP.